Development and Validation of the Human Aspects Influencing the Oral Healthcare Data Quality (HAI-DQ) Questionnaire among Primary Oral Healthcare Workers in Malaysia - Mohd Zuhudi, Alwani; Mohd Salleh, Syirahaniza; Sinor, Mohd Zulkarnain; Mat Nor, Mohd Zarawi; Ahmad, Basaruddin; Sanusi, Sarliza Yasmin (Journal of Dentistry Indonesia, 2024)
Resolving substandard oral healthcare data quality requires identifying the influencing factors. However, no known instrument for such assessment can be used locally. Objective: To develop and validate the HAI-DQ questionnaire for assessing human factors that influence oral healthcare data quality among primary oral healthcare workers in Malaysia. Methods: The HAI-DQ questionnaire was developed based on literature reviews, focus group discussions, and focus observations. Six experts assessed its content validity using the Content Validity Index (CVI), and the Face Validity Index (FVI) was used to establish its face validity through a pre-test involving 30 primary dental personnel. Results: Four domains with 57 items were derived during the HAI-DQ development. The I-CVI values between 0.83 to 1.00 and the S-CVI value of 0.97 indicated acceptable content validity. Excellent face validity was denoted by the I-FVI values of 0.93 to 1.00 and an S-FVI value of 0.99. Conclusion: HAI-DQ is relevant and comprehensible for assessing human aspects that influence data quality, indicating its potential to be used as an investigation tool in future research related to oral healthcare data quality. Nevertheless, other psychometric assessments are required to further support the instrument’s validity.